A high-emissive and stable luminescent silafluorene hybrid constructed by hydrosilylation. Issue 3 (March 2019) - Tang, Ping; Xiang, Kai; Wei, Huijie; Li, Shuhong; Xu, Caihong
Under Karstedt's catalyst, an organic–inorganic hybrid fluorescent nano-molecular dendrimer has been synthesized by grafting silafluorene units onto the polyhedral oligomeric silsesquioxane core through hydrosilylation reaction. The new hybrid molecule exhibits high solid fluorescence quantum efficiency because of the nano-size and large steric hindrance of the polyhedral oligomeric silsesquioxane core. Thermogravimetric analysis shows that the thermal stability of the target compound is effectively improved by the presence of polyhedral oligomeric silsesquioxane.